International trade in GMOs and GM products : national and multilateral legal frameworks - Zarrilli, Simonetta (UN New YorkUS, 2005)
Looks at domestic legislation on agro-biotechnology in selected developed and developing countries. Focuses on the multilateral legal framework. Deals with actual and potential GM-related trade disputes.